What type of leadership is more effective for managing change during force majeure? Achieving organizational effectiveness during the pandemic - Nazia Habib; Shaheryar Naveed; Muhammad Mumtaz; Rabia Sultana; Shoaib Akhtar (RAUSP Management Journal)
Purpose – Leaders have been facing serious challenges in managing organizations during COVID-19, which has brought the need for implementing sudden technological change across the globe. Hence, it was important to identify effective leadership styles to successfully manage the transformational process during the period. Therefore, the current study aims to explore and compare the effectiveness of transformational and ethical leadership (EL) in terms of achieving organizational goals during COVID-19 in public and private sector organizations in Pakistan. Design/methodology/approach – Comparative research was carried out to find out the effectiveness of transformational and EL during and pre-COVID-19 in public and private sector organizations using the lens of social exchange theory. Data was collected from 214 respondents representing 67.6% of public and 32.4% of private sector organizations of Pakistan at two different points in time. Detailed comparative analyses were conducted in AMOS version 24 to assess the effectiveness of leadership styles before and during COVID-19 times. Findings – On the whole, transformational leadership (TL) was found to have a greater impact on organizational effectiveness (OE) in comparison with EL in both pre-and during COVID-19 situations. Moreover, the effectiveness of TL significantly increased and the same decreased for EL during COVID-19. Additional analyses indicated that TL was effective for the private sector and EL for public sector organizations during COVID-19. Research limitations/implications – The study has not considered the mediating mechanisms of employee motivation, engagement and performance in the relationship between transformational and EL styles and OE, which can be explored in the future. Practical implications – These results have important implications for private and public sector organizations and suggest that the adoption of a TL style will generate better results in the private sector and an EL style in public sector organizations to achieve OE in uncertain situations such as COVID-19. Social implications – The study shows that leadership with more care and concern for humanity tends to perform better in terms of generating results for OE. Therefore, both transformational and EL are based on individualized consideration for employees and are effective during COVID-19 in private and public sector organizations in Pakistan. Originality/value – The study has carried out the comparative analyses in three different ways, including leadership styles (transformational and ethical), type of organization (private and public) and time frames (pre and during COVID-19), which is a true contribution of the research in the Pakistani context.